RESEARCH AND DEVELOPMENT OF THE SUKHOTHAI CREATIVE CITY CURRICULUM FRAMEWORK FOR HANDICRAFTS AND FOLK ARTS IN ALIGNMENT WITH THE MISSION OF MEMBERS OF THE CREATIVE CITY NETWORK ORGANIZATION FOR EDUCATION UNITED NATIONS SCIENCE AND CULTURE (UNESCO) - Wiwanthamongkon, Karanphon; Nukaew, Pornchai; Satpreetrai, Supalak; Kamuthapichai, Choowit; Kongkhao, Raya; Junsaipon, Theerapong (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This research aims to: (1) Analyze the framework development approach for the Sukhothai Creative City curriculum, (2) Develop and evaluate the quality of the curriculum framework, (3) Examine the implementation of the curriculum framework in school curriculum development, and (4) Define the effectiveness of the curriculum framework implementation and propose strategies for its broader application. This study employed a research and development (R&D) methodology, with the target group consisting of educational institutions in Sukhothai Province in the year 2021. A total of 51 institutions participated voluntarily through volunteer sampling. The research instruments included a questionnaire, an interview form, the Sukhothai Creative City curriculum framework document, a training manual for curriculum framework implementation, a curriculum quality assessment form, and a curriculum implementation monitoring form. The statistical methods used in the study included percentage, mean, standard deviation, and content analysis. The research results were found as follows: 1) The Sukhothai Creative City Curriculum Framework for Handicrafts and Folk Arts consists of 9 categories and has a manual for implementation. There is also training for educational institutions, focusing on practical work, together with supervision and monitoring of educational institutions. 2)The development of the Sukhothai Creative City curriculum framework document for school implementation was evaluated by experts, yielding an average appropriateness score of 0.84. 3) The implementation of the curriculum framework resulted in a training manual consisting of 4 chapters, totaling 18 hours. It was used and tested after training with an overall average score at a high level. A total of 57 courses were obtained with an overall quality at a high level. and 4)The effectiveness of the curriculum framework implementation in schools was rated at a high level. Recommendations were made to enhance the system and mechanisms for broader and more effective implementation.